MP57: Effect of grip strength measured in the emergency department on the risk of functional decline following a minor trauma in robust elderly: a pan-Canadian study. (May 2020) - Hegg, S.; Sirois, M.; Carmichael, P.; Perry, J.; Lee, J.; Daoust, R.; Lang, E.; Emond, M.
Abstract : Introduction: The elderly (65 yo and more) increase in Canada is well documented along with a disproportionate use of Emergency Departments after a minor injury. These patients requires specific care given a 16% risk of functional decline following a visit to ED. To prevent functional decline, a multidimensional assessment of the elderly is recommended in the emergency department. Objective: To determine if ED grip strength can predict functional decline at 3 or 6 months post-injury. Methods: A multicentre prospective study in 5 ED across Canada was realized between 2013 and 16. Patients 65 years old and over, autonomous in daily living activities and consulting the emergency department for minor trauma were recruited 7 days a week. Clinical-demographic data, functional status, fear of falling, number of falls in the last month, grip strength measurement were collected in the ED. Functional decline (loss of at least points to functional status) was calculated at 3 and 6 months. Descriptive statistics and linear regression model with repeated measurements were used to determine if the grip strength was predictive of functional decline at 3 or 6 months. Results: 387 patient were recruited. Mean age was 74 ± 7 years old, 52% were male. XXX experienced a fall in the last month. The initial maximum grip strength was (24 ± 10 intervention vs. 28 ± 13 control; p ≤ 0.05). grip strength is associated with pre-injury functional status (p < 0.0001) and fear of falling (p = 0.0001) but does not predict 3 or 6 month functional decline. Conclusion: Given the strong association with fear of falling and functional status at initial ED evaluation, we recommend that grip strength measurement could be included in a multidisciplinary geriatric emergency department assessment as needed.